Self-powered miniature liquid treatment system - Baarman, David W; Leppien, Thomas; Lautzenheiser, Terry Lee; Houghton, Christopher B; McPhilliamy, Stephen J (2010)
A liquid treatment system that may be self-powered includes a filter, an ultraviolet light source and a hydro-generator. A flow of liquid may be filtered with the filter and used to rotate the hydro-generator to generate electric power. The ultraviolet light source may be energized by the electric power generated by the hydro-generator when the magnitude of electric power of the hydro-generator enters a determined range. The flow of liquid may be subject to ultraviolet energy generated by the ultraviolet light source.